Experimental and Numerical Analysis of the Effect of Components on a Double-Sided PCB on LED Junction Temperature and Light Output Using CFD - Sökmen, Kemal Fürkan; Karatas, Osman Bedrettin (Springer Heidelberg, 2020)
In today's lighting industry, with developing technology and a widened usage area, LEDs have become very popular due to their higher energy efficiency and longer life. In the present study, the effect of electronic components on printed circuits and the radiation level on light output was studied. The performed analysis was validated with an experimental method. For the finite volume method, FloEFD 2019, commercial software, was used. The ambient temperature was assumed to be 23 degrees C. The value of solar irradiance was taken as 1009 W/cm(2). LEDs on a PCB were driven at 70 mA at first and then at 50 mA, and, by exerting power on all electronic components, analyses were performed. Both sides of the PCB were examined, and, in order to achieve efficient heat conduction, the power and distribution of the electronic components on the back side of the LEDs were optimized. With a new electronic circuit design, analyses were performed at 50, 55, 60, 65, and 70 mA. It was determined that the highest light output was achieved at 65 mA and that the distribution of electronic components on a PCB indirectly affects light output through junction temperature (T-j).
Keywords: LED automotive lamp; Laminar natural convection; Computational fluid dynamics (CFD); Junction temperature; Monte Carlo radiation